Plasmolipin deficiency is essential for HUVECs survival under hypoxic conditions - Yanghua Li; Weiling Man; Xiang Li; Xiaojie Wu; Yumeng Cui; Shiyun Chen; Xianhong Li; Yanli Lin; Lihe Jiang; Youliang Wang (Cell Death Discovery)
Abstract This study aims to explore the molecules that affect the survival of Human Umbilical Vein Endothelial Cells (HUVECs) under hypoxia and their mechanisms of action. In hypoxia, plasmolipin (PLLP) was identified through the screening of CRISPR/Cas9 and small guide RNA (sgRNA) library. Functionally, PLLP knockout led to increase cell proliferation, cellular metabolism, tight junction formation, angiogenesis ability, migration and invasion in hypoxic HUVECs. Furthermore, PLLP knockout countered the inhibitory effects of bevacizumab on HUVECs angiogenesis and cell survival in hypoxic conditions. PLLP knockout was found to modulate the survival of HUVECs in hypoxia by enhancing the phosphorylation of AKT and ERK1/2 proteins. In conclusion, inhibiting the expression of PLLP in HUVECs promotes cell survival and maintenance of cellular functions under hypoxic condition. PLLP plays a crucial role in regulating cell survival in hypoxia through the activation of AKT and ERK1/2 pathways. This study identifies novel molecules that affect HUVECs survival under hypoxic conditions and provides a new possibility for future studies on cell survival under hypoxic conditions.